Perancangan Sistem Informasi Pembayaran SPP Berbasis Web : Studi Kasus Pada : Pondok Pesantren Darul Musthofa Wirosari-Grobogan - Anita Rusmiati; Maya Utami Dewi; Siti Kholifah; Siswanto Siswanto (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
Darul Musthofa Wirosari Grobogan Islamic Boarding School is a boarding school where the tuition payment system still uses a manual system which later the administration section will make a report to the head of the boarding school. The formulation of this problem is an information system so that there is no double recording and books are easily torn so that transaction records are easily lost. The purpose of this study is to create a tuition payment information system to facilitate the creation of reports/data recording is still manual in books. As well as a summary of data one by one manually which results in recording taking a long time. The system developed in this study is web-based visual code software, storage is one in a MySQL database and makes it easy for users to record tuition fees with accurate results so as to reduce the risk of errors, loss and data manipulation